Managing generalized interferon‐induced eruptions and the effectiveness of desensitization. Issue 5 (May 2014) - Poreaux, C.; Bronowicki, J.‐P.; Debouverie, M.; Schmutz, J.‐L.; Waton, J.; Barbaud, A.
Summary Background We evaluated the value of skin tests and the efficacy of a 12‐step desensitization protocol to pegylated interferon (IFN) in patients with generalized drug eruptions due to IFNs. Methods A retrospective study (1998–2009) was followed by a cross‐sectional clinical study conducted prospectively (2009–2011). All patients received a dermatological clinical examination and skin tests. Twelve‐step IFN desensitization was proposed for patient with active hepatitis C and no alternative therapy. Results Twenty‐six patients (13 males, mean age, 53.5 years) had generalized reactions to IFNs; 21 were treated with IFN‐α and 5 with IFN‐β. Moreover, 21 patients had skin tests. Intradermal tests (IDTs) were positive after an average of 72 h. Cross‐reactivity between peg‐IFN‐α2a and peg‐IFN‐α2b was observed in 5/10 cases in the prospective study. In 16 of 26 cases, IFN treatment was stopped. In 8 of 16 cases of diffuse eczematous drug eruption, treatment was continued. The corticosteroid and antihistamine were sufficient in 4/8 cases. In three other cases, topical tacrolimus was highly effective. In 3 of 16 cases in which treatment were stopped, patients underwent the early resumption of peg‐IFN‐α. These three patients had positive tests with peg‐IFN‐α2a and peg‐IFN‐α2b and successfully completed the tolerance induction protocol for peg‐IFN‐α2b. Tolerance induction involved a weekly dose of peg‐IFN and a gradual increase in the recovery of an antiviral C. Clinical tolerance was excellent, and the patients' viral load C became negative. Conclusions Our study demonstrates the benefit of allergy testing in cases of generalized drug reactions to IFN, cross‐reactivities in a single class of IFNs and the importance of delayed IDT reading. We report for the first time the effectiveness of 12‐step desensitization with peg‐IFN.